Review about effects of IOT and Nano-technology techniques in the development of IONT in wireless systems - Mezaal, Yaqeen S.; Yousif, Lujain N.; Abdulkareem, Zahraa J.; Hussein, Hussein A.; Khaleel, Shahad K. (International Journal of Engineering and Technology, 2018)
The growing and constantly emerging technology trends has increased the use of devices day by day and hence the efforts have been made to connect every device with each other through internet which is being called as Internet of Thing (IoT). Precisely, IoT is inter-networking of substantial tools, constructions and other items. Nanotechnology is the study and manufacture of extremely tiny machines or devices ranging from 1 to 100 nanometres. It has provided possible effectual solutions to numerous uses in biomedical, industrial, agricultural and military applications. On the other hand, nanosensors are any organic, biochemical, or clinical sensory points used to transfer information about nanoparticles to the macroscopic domain. The nano devices and nanosensors interconnection with Internet has pioneered the expansion of subsequent generation criterion derived from IoT known as â€œInternet of Nano Thingsâ€ (IoNT). The foremost goal of this study is to give a comprehensive attitude of IoNT, its architecture, advantages, tryouts, application scopes and look out the prospects about how we can overcome the challenges and make the use of Internet of NanoThings in the field or wireless engineering. Additionally, IoT, Internet of Every-thing (IoE) and IoNT bases are discussed in this review.